2016
DOI: 10.1370/afm.1929
|View full text |Cite
|
Sign up to set email alerts
|

Concept Mapping as a Method to Engage Patients in Clinical Quality Improvement

Abstract: Patient engagement has become a primary care research and practice priority. Little guidance exists, however, on how best to engage patients in primary care practice improvement, or how to measure the impact of their engagement. We present an overview of group concept mapping as a method for engaging patients in primary care practice improvement. We detail the group concept mapping process as a tool for use in primary care practice improvement, research, and evaluation, and we present resources to enable resea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 23 publications
(23 reference statements)
0
27
0
1
Order By: Relevance
“…While its origins are in evaluation and planning, it has been used to address health care issues [ 44 , 45 ]. Group concept mapping is well suited to garnering the views of a broad group of people, has the potential to capture and represent stakeholder groups, is uniquely suited to community-engaged research [ 36 , 46 ], and is identified as an effective methodology for engaging patients in clinical improvement activities [ 47 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…While its origins are in evaluation and planning, it has been used to address health care issues [ 44 , 45 ]. Group concept mapping is well suited to garnering the views of a broad group of people, has the potential to capture and represent stakeholder groups, is uniquely suited to community-engaged research [ 36 , 46 ], and is identified as an effective methodology for engaging patients in clinical improvement activities [ 47 ].…”
Section: Methodsmentioning
confidence: 99%
“…Cluster analysis is a statistical technique used to develop a higher order understanding of the relationship between statements represented in the point map. The process involves drawing a set of boundaries on the point map to create different numbers of clusters [ 47 ]. Bridging values for each statement identified which statements are anchoring -sorted primarily with others close by, and which are bridging - sorted with others across a larger area of the map.…”
Section: Methodsmentioning
confidence: 99%
“…It has also been used to engage patients in clinical quality improvement. 21 We report on the first phase of concept mappingbrainstorming -which engages participants in generating ideas relevant to the research question. Research has shown that brainstorming in group concept mapping is highly effective and efficient at identifying outcomes important to patients compared to traditional qualitative methods.…”
Section: Study Design and Participantsmentioning
confidence: 99%
“…Primary care practices have started to explore different methods of engaging with patients to advance quality improvement. 6 The authors' primary care Family Health Team (FHT) organisation chose to leverage methods of citizen engagement to develop and host a 1-day patient engagement event designed to gather feedback on core services. 7 To the authors' knowledge, there has been no empirical research to understand the impact of such an approach; therefore, the authors undertook a rapid ethnographic evaluation of the event to understand its impact and what context and mechanisms might relate to potential success.…”
Section: Introductionmentioning
confidence: 99%